171. DELAYED DIAGNOSIS OF EOSINOPHILIC ESOPHAGITIS IN THOSE PRESENTING TO THE EMERGENCY DEPARTMENT WITH FOOD BOLUS IMPACTION. (24th September 2022) - Gyimah, Dominic Ayi; Khan, Humza; Abdalla, Badr; Haboubi, Hasan
Abstract: Food bolus impaction can be a manifestation of chronic untreated inflammation in those with underlying eosinophilic esophagitis (EoE). The eosinophil predominant inflammation of the esophagus is associated with a higher prevalence of fibrosis when it remains undetected and untreated. Non-malignant food bolus impaction is strongly associated with an underlying diagnosis of EoE, but outside of gastroenterology and other esophageal interested specialists there remains poor understanding of how to diagnose and manage this condition. We conducted a retrospective study of patients presenting to a tertiary emergency unit with esophageal food bolus impaction between November 2018 and May 2021. Electronic attendance records and the endoscopy database were examined to determine the associations between demographics, comorbidities, endoscopic findings, biopsy findings and follow up. We also evaluated the effect of the pandemic on food bolus management with statistical analysis undertaken using IBM SPSS software. Of the 938 patients who presented to the emergency department with food bolus impaction, 83.6% were sent home with no follow up. Only 7.2% went on to have an endoscopy. In those with macroscopic evidence of inflammation, only 35.8% of patients had the correct number of biopsies taken to establish a histological cause for their symptoms. 1.6% of patients demonstrated histological evidence of EoE, of whom 80% were male and 20% female. The COVID-19 lockdown did not negatively impact access to endoscopy with mean wait time improving from 121-days prior to lockdown compared to 69-days during lockdown, p < 0.01. Our findings highlight significant shortcomings in the management of those presenting emergently with food bolus impaction and possible undiagnosed EoE. There remains a need for clear management pathways to aid risk-stratification, discharge planning and endoscopic practices in the diagnosis of EoE. We therefore propose an algorithm for food bolus management to facilitate early endoscopy, effective diagnosis, and appropriate follow-up, ensuring optimal management for patients with non-malignant dysphagia requiring emergency admission for resolution of food impaction.